Climatic Water Balance Comparison for Selected areas in The Middle of Iraq - Muhammad, Samah Abdullah; Al-Dabbas, Moutaz (Iraqi Journal of Science, 2022)
The climate parameters annual rainfall and average mean temperature are investigated from 2000 to 2019 for Kut, Hilla and Iskandaryia. Evidence of climate change is noticed by decreasing the mean annual rainfall and relative humidity with an increase in the annual mean temperature. The climate water balance has been calculated. Due to high temperature, increased evaporation, and low precipitation rates, there was a large water deficit. The total water surplus in the Kut area is 32.86 mm from November to February, and in  Hilla and Iskandaryia is 20.4 and 27.8 mm from December to February, respectively. The climate classification for the three stations was semi-dry to dry climates. The region has a significant water deficit of up to 79.6 % of the total rainfall values indicated in Hilla station. Climate change has affected the locations near meteorological stations such as Kut, Hilla and Alexandria. All the studied climatic variables imprint water surplus or water deficit with slight changes within each geographical area.